If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(K + -86) = 36 Reorder the terms: 6(-86 + K) = 36 (-86 * 6 + K * 6) = 36 (-516 + 6K) = 36 Solving -516 + 6K = 36 Solving for variable 'K'. Move all terms containing K to the left, all other terms to the right. Add '516' to each side of the equation. -516 + 516 + 6K = 36 + 516 Combine like terms: -516 + 516 = 0 0 + 6K = 36 + 516 6K = 36 + 516 Combine like terms: 36 + 516 = 552 6K = 552 Divide each side by '6'. K = 92 Simplifying K = 92
| 39+x-9*3=25 | | 37=7d-26 | | 4.5(x+2.4)=-13.5 | | 1/7x-8=-3 | | 21+7h=91 | | 9x+3(5x+y)=15 | | 1/3*7/8 | | 88=8(b+2) | | 15x-10=5(2x-7) | | 4z-4=8 | | (8-5)+2x+(3x-10)=180 | | 4a+3=2x | | 13=4t+5 | | 3(p+6)(p+5)=0 | | 5x-2x=4 | | 4p=4p-12 | | -2/5(x-4)=-2 | | 0.5y-0.1(y+3)=0.2(2y+1)-0.7 | | 10+3d=19 | | 13-2m=7 | | 1/2*2/8 | | 0.5y-0.1(y+3)=0.2 | | 4m-23=-27+5m | | y-52/6=5 | | b^0=0 | | b^0=1 | | 8b+12=92 | | 1/2y-7/2=-1/3y-5 | | j-357/18=30 | | b^1=0 | | 20-2k=12 | | x^2+6x-3=-3 |